Building with earth; an exploration on contemporary earth architecture - Da Silva Melo Miguez, Carolina (My University, 2025)
In response to the climate crisis, the building industry must fundamentally rethink how materials are sourced and used. As the environmental impact of conventional construction becomes increasingly evident, this thesis investigates the potential of earth as a sustainable, low impact building material. Urban areas generate significant amounts of excavated soil from construction activities, which are often discarded as waste. However, this material holds immense potential for reuse in building construction. The focus of this thesis is to examine how earth can be used in highly urbanized and industrialized contexts to support sustainable densification, particularly in urban gaps. Drawing on the rich history of earthen construction, this research explores the viability of clay and soil as future circular building materials. Earth is abundant, infinitely recyclable, and has a low carbon footprint, offering an alternative for large-scale modern construction. The design component of this thesis proposes a residential building in the Masthugget district of Gothenburg, Sweden, employing earth-based construction techniques in a materialdriven approach to design, demonstrating how earth can meet both contemporary standards and environmental goals. Ultimately, this project seeks to showcase the transformative potential of earth as a building material, both for its minimal environmental impact and for the powerful narrative it brings to the future of architecture
Keywords: Earth architecture, Low-impact materials, Life Cycle Assessment, Sustainable housing, Urban densification